2018
DOI: 10.3847/1538-4357/aabae5
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limits on the Presence of Central Massive Black Holes in Two Ultra-compact Dwarf Galaxies in Centaurus A

Abstract: The recent discovery of massive black holes (BHs) in the centers of high-mass ultra-compact dwarf galaxies (UCDs) suggests that at least some are the stripped nuclear star clusters of dwarf galaxies. We present the first study that investigates whether such massive BHs, and therefore stripped nuclei, also exist in low-mass (M<10 7 M e ) UCDs. We constrain the BH masses of two UCDs located in Centaurus A (UCD 320 and UCD 330) using Jeans modeling of the resolved stellar kinematics from adaptive optics data ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 103 publications
(217 reference statements)
2
41
1
Order By: Relevance
“…For UCD 320, Voggel et al (2018) reported a singlecomponent structure (perhaps indicative of a globular cluster rather than a UCD galaxy), with M V = −10.39 mag and M * /L V = 2.64, and therefore one obtains a total stellar mass of 3.17 × 10 6 M . If this is a remnant nuclear star cluster, then from equation 9 one may expect it to contain a black hole with a mass equal to 5.5 × 10 4 M , i.e.…”
Section: Centaurus A: Ucd 320 and Ucd 330mentioning
confidence: 99%
“…For UCD 320, Voggel et al (2018) reported a singlecomponent structure (perhaps indicative of a globular cluster rather than a UCD galaxy), with M V = −10.39 mag and M * /L V = 2.64, and therefore one obtains a total stellar mass of 3.17 × 10 6 M . If this is a remnant nuclear star cluster, then from equation 9 one may expect it to contain a black hole with a mass equal to 5.5 × 10 4 M , i.e.…”
Section: Centaurus A: Ucd 320 and Ucd 330mentioning
confidence: 99%
“…The comparison to known NSC-type UCDs shows that these are more massive, bigger and denser than FCC 47-UCD1. As UCDs are considered to be unrelaxed systems (Fellhauer & Kroupa 2002;Norris & Kannappan 2011;Voggel et al 2018), a colour gradient translates directly into a population gradient (instead of being an effect of mass segregation), where a slightly younger population is found at the center while the outskirts are dominated by a older, metal-poor population. Although we cannot find a significant colour gradient, we find the UCD to appear larger in the blue than the red filter by ∼ 10%, corresponding to a more extended metal-poor population.…”
Section: Ucd Propertiesmentioning
confidence: 99%
“…Both, top-heavy (Murray 2009;Dabringhausen et al 2009) and bottom-heavy IMFs (Mieske & Kroupa 2008) are discussed. While a SMBH presents a different explanation for the elevated M/L dyn for high mass UCDs (Mieske et al 2013), a search for SMBHs in two lower-mass UCDs (< 10 7 M ) around Centaurus A yielded a nondetection (Voggel et al 2018). Because of detection thresholds, the non detection of a central BH; however, does not disqualify a UCD from being a former nucleus of an accreted low-mass dwarf galaxy.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Supermassive black holes are found in most, but crucially not all, galactic nuclei. Perhaps all, and certainly most, nuclei also host a nuclear stellar cluster at the very centre (Neumayer & Walcher 2012, Voggel, et al 2018, Voggel et al 2019, Nguyen et al 2019. Intriguingly, some galactic nuclei are found to contain a nuclear stellar cluster but show no evidence for a supermassive black hole.…”
Section: Introductionmentioning
confidence: 99%